Teachers’ Performance Evaluation Instrument Designs in the Implementation of the New Learning Paradigm of the Merdeka Curriculum - Kasman Kasman; Siti Khodijah Lubis (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This research aims to design an instrument for evaluating teachers’ performance in the implementation of the new learning paradigm of the Merdeka Curriculum. This research employed a qualitative approach with a literature study method. This research data is secondary data collected through the exploration of sixty-four literary references from books and articles in nationally accredited and internationally reputable scientific journals. The data were analyzed by using Miles’ and Huberman’s interactive model, which includes data reduction, data presentation, and conclusion drawing/verification. The results of this study indicated that the design of the teacher performance evaluation instrument in the new learning paradigm of the Merdeka Curriculum take into account teachers’ planning, implementation and assessment of the learning. Lesson planning is evaluated based on the comprehensiveness of the components contained in the teaching modules composed by a teacher. The teaching module must contain indicators of general information and core components. The instrument utilized is a documentation review using a checklist sheet with a Guttman scale. The implementation of the learning is evaluated based on the teachers’ learning practices, using the indicators of the teachers’ skills in preliminary activities, core activities and closing activities. The instrument utilized in this case is an observation sheet in the form of a rubric with a 4-point Likert scale. The evaluation of the learning process is referred to as an assesssment, using the learning assessment indicators include diagnostic, formative, summative, and assessment principles and components. Teachers’ performance evaluation instruments designs in the implementation of the new learning paradigm of the Merdeka Curriculum was serve as a reference in conducting evaluations. Through performance evaluation, teachers’ competencies can be measured, learning obstacles can be identified, feedback on classroom needs can be provided, and opportunities for schools and teachers to develop themselves can be created.